Respuesta :

Answer:

2.) (3,-2)

3.) (5,3)

4.) *Still trying to solve*

Step-by-step explanation:

2.)

Step 1.

   5x + 4y = 7

    3x - 4y = 17

+ ------------------

    8x      =   24

    8              8

         x = 3

Step 2.

    5x + 4y = 7

    5(3) + 4y = 7

     15 + 4y = 7

     -15          -15

      4y =  -8

      4        4

        y = -2

Final Answer: (3,-2)

3.

Step 1.

    4x + 5y = 35

         x = 2y - 1

   4(2y - 1) + 5y = 35  

    8y - 4 + 5y = 35

      13y - 4 = 35

            +4     +4

        13y = 39

        13      13

        y = 3

Step 2.

    x = 2y - 1

    x = 2(3) - 1

     x = 6 - 1

     x = 5

Final Answer: (5,3)

I do apologize that I couldn't find the solution to 4.) if I do I will edit this answer

I hope this helps!